Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1105/tpc.004853
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Proline-Mediated Tolerance to Toxic Heavy Metals in Transgenic Microalgae

Abstract: Pro has been shown to play an important role in ameliorating environmental stress in plants and microorganisms, including heavy metal stress. Here, we describe the effects of the expression of a mothbean delta(1)-pyrroline-5-carboxylate synthetase (P5CS) gene in the green microalga Chlamydomonas reinhardtii. We show that transgenic algae expressing the mothbean P5CS gene have 80% higher free-Pro levels than wild-type cells, grow more rapidly in toxic Cd concentrations (100 microM), and bind fourfold more Cd th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
236
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 455 publications
(259 citation statements)
references
References 31 publications
12
236
1
1
Order By: Relevance
“…5a & b), suggesting that both proline and betaine protect against Cd-dependent oxidative damage by enhancing antioxidant defense and MG detoxification systems (Demiral and Türkan 2004;Okuma et al 2004;Park et al 2006;Huang et al 2009;Hossain and Fujita 2010). Similar findings have been reported by other researchers demonstrating higher Cd tolerance by in vivo betaine or proline synthesis in plants (Siripornadulsil et al 2002;Shao et al 2008). …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…5a & b), suggesting that both proline and betaine protect against Cd-dependent oxidative damage by enhancing antioxidant defense and MG detoxification systems (Demiral and Türkan 2004;Okuma et al 2004;Park et al 2006;Huang et al 2009;Hossain and Fujita 2010). Similar findings have been reported by other researchers demonstrating higher Cd tolerance by in vivo betaine or proline synthesis in plants (Siripornadulsil et al 2002;Shao et al 2008). …”
Section: Discussionsupporting
confidence: 83%
“…An increase in GSH content due to proline pretreatment and lower lipid peroxidation has recently been reported (Xu et al 2009). Transgenic plants for higher proline and betaine biosynthesis also showed higher GSH, GSH/GSSG ratio and lower GSSG content as compared to wild-type under Cd medium and other stress conditions (Siripornadulsil et al 2002;Yang et al 2007). Therefore, both proline and betaine might play a significant role in maintaining higher GSH level either through efficient recycling or by modulating higher GSH synthesis (Kocsy et al 2005;Hossain and Fujita 2010).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We also observed that proline preserves the intracellular glutathione pool, which is the major redox buffer of the cell. Proline protection of GSH was previously observed in Chlamydomonas reinhardtii exposed to toxic Cd levels [60]. Thus, proline accumulation appears to be an effective means for protecting the glutathione redox state of the cell under stress conditions perhaps by directly scavenging ROS.…”
Section: Discussionmentioning
confidence: 72%
“…Acetyl-CoA carboxylase (ACC) catalyzes the biotin-dependent carboxylation of acetyl-CoA to produce malonyl-CoA. This is the first and the committed step in the biosynthesis of long-chain fatty acids [10].…”
Section: Biofuel Productionmentioning
confidence: 99%